28 June Sarajevo 1914--Versailles 1919 : the war and peace that made the modern world - Sharp, Alan (Makers of the modern world, 2014)
The Makers of the Modern World, 28 June looks in greater depth at the smaller nations that are often ignored in general histories, and in doing so seeks to understand the conflict from a global perspective, asking not only how each of the signatories came to join the conflict but also giving an overview of the long-term consequences of their having done so.